The Development of Toddlers in Russia: Needs and Trends - Mikhail Volchanskiy (Journal of Global Pharma Technology, 2016)
The level of physical development of children reflects their health status. The goal is to evaluate the anthropometric indicators of toddlers aged 1-3 in Moscow as a sample model of Russia and to identify gender and age differences. The studies were conducted in 2017-2019 in Moscow (Russian Federation). On the basis of 10 pediatric clinics, 3000 children were selected, of which 1650 boys and 1350 girls of toddler age, 1-3 years old. 4 anthropometric parameters were regularly measured (body length, body weight, circumference of the chest and head). Significant differences in all anthropometric parameters were found to be large for boys compared to girls. In boys, there was a 9.0 cm difference in body length between 2 and 1 years (p ≤ 0.001), and 10.0 cm between 3 and 2 years (p ≤ 0.001). In girls, the results were identical (p ≤ 0.001). Boys aged 2 were 2.6 kg heavier than one-year-olds (p ≤ 0.001), and at the age of three they were 1.8 kg heavier than two-year-olds (p ≤ 0.001). Girls aged 2 had body weight 2 kg more than one-year-olds (p ≤ 0.001), and 3-years-olds were 1.3 kg (p ≤ 0.01) heavier compared with two-years-olds. The chest circumference in boys aged 2 is 2.5 cm larger than in one-year-olds, and 1.5 cm (p ≤ 0.001) smaller than in toddlers aged 3. In girls the differences were 2.5 cm and 1.2 cm, respectively (p ≤ 0.01). The head circumference for boys aged 2 was 2 cm more than the parameters of one-year-olds (p ≤ 0.001), and for boys aged 3 - 1 cm more than two-year-olds (p ≤ 0.001). For girls the differences were 2 cm between ages of 1 and 2, and 1 cm between ages of 2 and 3 (p ≤ 0.001). The research results can be adapted when creating a single database of world data to identify the processes of acceleration or deceleration and the factors that determine them. The processes of changing anthropometric indicators were identified for toddlers aged 1-3. Three anthropometric indicators (head and chest circumference, body length) in boys and girls change with the same growth rate over time. The fourth indicator, body weight, changes somewhat faster in boys (0.8 kg versus 0.7 kg in girls, p ≤ 0.05). The remaining three indicators significantly differ within groups of boys and girls between age groups (p ≤ 0.001). Thus, age differences prevail over gender differences. Keywords: Early childhood, Regional standards, Socio-economic factors, Anthropometry, Body weight, Body length, Chest circumference, Head circumference.